ENSIKLOPEDIA BUDAYA SUKU MANGGARAI BERBASIS WEBSITE PADA DINAS BUDAYA DAN PARIWISATA KOTA RUTENG - Yaputra, Valentino Raindi; Lamabelawa, Marinus I. J. (Lembaga Pengembangan Kinerja Dosen, 2026)
Indonesia, as an archipelagic country rich in cultural diversity, has a cultural heritage that reflects the nation's identity. One of the tribes that has a unique cultural wealth is the Manggarai Tribe in Manggarai Regency, East Nusa Tenggara. This cultural wealth includes dance, music, weaving, food, and unique traditional ceremonies. However, modernization and lack of appreciation from the younger generation threaten the sustainability of this culture. For this reason, the development of a website-based cultural encyclopedia is a strategic step in documenting, preserving, and promoting the culture of the Manggarai Tribe. This study aims to design a website-based digital encyclopedia that focuses on traditional Manggarai dances, such as the Caci Dance, Penti Dance, Rangkuk Alu Dance, Ndundu loka Dance, Congka sae Dance, Danding Dance, Ndundu Ndake Dance and Tiba Meka Dance, and the data taken is in the form of videos, images and also the history of the dance, in order to understand the symbolic meaning behind them. It is hoped that this encyclopedia can increase cultural awareness, facilitate dialogue between generations, and support the promotion of culture and culture-based tourism in Manggarai Regency. This research focuses on the planning, design, content and development process of digital platforms using information technology, with the subject of Manggarai culture and the research location in Ruteng City. Through this encyclopedia, the cultural heritage of the Manggarai Tribe can continue to live on and be known to future generations. The system development method used is the Waterfall method which includes requirements analysis, design, implementation, testing and maintenance. This research is hoped to give construction of a website Encyclopedia of Manggarai Tribe, especially on dance.